2006
DOI: 10.1016/j.susc.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel mesoscale defect structure on NiO(100) surfaces by atomic force microscopy

Abstract: Part of the Chemistry CommonsThis Article is brought to you for free and open access by the Published Research -Department of Chemistry at DigitalCommons@University of Nebraska -Lincoln. It has been accepted for inclusion in Marjorie A. Langell Publications by an authorized administrator of DigitalCommons@University of Nebraska -Lincoln.Petitto, S. C.; Berrie, Cindy L.; and Langell, Marjorie , "Novel mesoscale defect structure on NiO(1 0 0) surfaces by atomic force microscopy" (2006). Marjorie A. Langell Publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Motivated in large part by understanding spin dynamics in antiferromagnetic materials, several AFM studies of NiO(100) surfaces in which atomic resolution has been obtained have been reported in the literature in recent years. The AFM images obtained in these studies provide a picture of the NiO(100) surface that is similar to that described above for MgO(100). The NiO(100) surface is found to not reconstruct and has a periodicity consistent with ideal termination of the bulk .…”
Section: Metal Oxides With Rock Salt Structurementioning
confidence: 90%
See 2 more Smart Citations
“…Motivated in large part by understanding spin dynamics in antiferromagnetic materials, several AFM studies of NiO(100) surfaces in which atomic resolution has been obtained have been reported in the literature in recent years. The AFM images obtained in these studies provide a picture of the NiO(100) surface that is similar to that described above for MgO(100). The NiO(100) surface is found to not reconstruct and has a periodicity consistent with ideal termination of the bulk .…”
Section: Metal Oxides With Rock Salt Structurementioning
confidence: 90%
“…The NiO(100) surface is found to not reconstruct and has a periodicity consistent with ideal termination of the bulk . Wide scan images of cleaved NiO(100) surfaces show that the dominant defect structures are step edges aligned along the ⟨001⟩ and ⟨010⟩ crystallographic directions. , …”
Section: Metal Oxides With Rock Salt Structurementioning
confidence: 97%
See 1 more Smart Citation
“…The surface properties of transition-metal oxides have been widely studied due to their application in the fields of solid-state electronic devices, storage media, and catalysts. It is well-known that the surface properties of transition-metal oxides are strongly correlated with both the surface stoichiometry (instantiated by the oxygen or cation vacancies, adatoms ) and the mesoscopic scale defects (such as the step-defects , and pits , ). The modulation of surface stoichiometry and the incorporation of defects are generally realized by the chemical corrosions, , high-temperature annealing, , ion sputtering, , and the lattice mismatch .…”
Section: Introductionmentioning
confidence: 99%
“…The surface properties of transition-metal oxides have been widely studied due to their application in the fields of solid-state electronic devices, storage media, and catalysts. It is well-known that the surface properties of transition-metal oxides are strongly correlated with both the surface stoichiometry (instantiated by the oxygen or cation vacancies, adatoms ) and the mesoscopic scale defects (such as the step-defects , and pits , ). The modulation of surface stoichiometry and the incorporation of defects are generally realized by the chemical corrosions, , high-temperature annealing, , ion sputtering, , and the lattice mismatch . Although these technical means can easily alter the surface stoichiometry, the distribution of the defects is often arbitrary, constantly resulting in the ungovernable properties of the surface.…”
Section: Introductionmentioning
confidence: 99%